School–Community Partnership and Its Influence on Learners’ Academic Achievement - Cabral, Richard; Montallana, Gilbert; Tiunayan, Silryann; Villacarillo, Irwin Roberto; Adao, Joan (International Journal of Sustainability and Advanced Integrated Research, 2026)
This study examined the relationship between school–community partnership and learners' academic achievement in selected public schools in the Taft District. Guided by Bronfenbrenner's Ecological Systems Theory and Epstein's Theory of Overlapping Spheres of Influence, the study focused on four dimensions of school–community partnership: parental involvement, community participation, shared decision-making, and resource mobilization. A descriptive-correlational research design was employed. Data were collected from teachers and school administrators using a researcher-made questionnaire, while learners' academic achievement was measured through school records. The questionnaire underwent expert validation and demonstrated acceptable reliability (Cronbach's alpha = 0.81). Descriptive and inferential statistics, including the Pearson Product-Moment Correlation, were used to analyze the data. The findings revealed that school–community partnership was generally high, with parental involvement receiving the highest rating. Learners from schools with stronger partnerships achieved higher academic performance than those from schools with lower partnership levels. The study further identified a statistically significant difference in academic achievement between schools with low and high levels of partnership and established a strong positive relationship between school–community partnership and learners' academic achievement. Among the partnership dimensions, parental involvement exhibited the strongest association with academic performance, followed by resource mobilization, community participation, and shared decision-making. The study concludes that strengthening collaboration among schools, families, communities, and other stakeholders contributes positively to learners' academic achievement. It recommends enhancing stakeholder participation, strengthening parental engagement, expanding community partnerships, institutionalizing effective partnership practices, and exploring additional factors influencing academic performance in future studies. This study supports Sustainable Development Goal 4 (Quality Education) by promoting collaborative approaches that improve learning outcomes and Sustainable Development Goal 17 (Partnerships for the Goals) by emphasizing shared responsibility among educational stakeholders. The findings contribute to educational sustainability by providing evidence that supports stronger school–community collaboration, informed educational policies, and sustained stakeholder engagement to improve learner outcomes.
Keywords: Academic Achievement; Community Participation; Parental Involvement; Resource Mobilization; School–Community Partnership; Shared Decision-Making